2019
DOI: 10.20546/ijcmas.2019.804.136
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Certain Chickpea Genotypes against Pulse Beetle, Callosobruchus chinensis (L.) under Laboratory Conditions

Abstract: A laboratory experiment was conducted to determine the resistance of 15 chickpea genotypes against pulse beetle, Callosobruchus chinensis (L.) under laboratory conditions. The mean per cent weight loss ranged from 62.48 to 33.92 per cent. The genotype PBG 5 (33.92%) recorded minimum per cent weight loss followed by GNG 469 (34.16%) and these were identified as tolerant genotypes. Whereas, the genotype Chaffa recorded highest per cent weight loss (62.48 %) followed by H 82-2(HC-1) (49.04%) and these were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…Current findings are in agreement with Sharma et al (2023) who found reduction in carbohydrates in chickpea grains after C chinensis infestation. Results of this study are similar to those of Deepika et al (2020) who found carbohydrates loss from 37.67 to 48.65%. Current finding is partially consistent with the findings of Saxena and Saxena (2011) who stated 45 to 54% carbohydrate content reduction after 6 months of pest infestation.…”
Section: Carbohydratessupporting
confidence: 89%
See 1 more Smart Citation
“…Current findings are in agreement with Sharma et al (2023) who found reduction in carbohydrates in chickpea grains after C chinensis infestation. Results of this study are similar to those of Deepika et al (2020) who found carbohydrates loss from 37.67 to 48.65%. Current finding is partially consistent with the findings of Saxena and Saxena (2011) who stated 45 to 54% carbohydrate content reduction after 6 months of pest infestation.…”
Section: Carbohydratessupporting
confidence: 89%
“…These findings are according to Allali et al Results of qualitative parameters depicted that protein contents reduced from 10.56 to 23.02% in chickpea varieties. Deepika et al (2020) noticed protein content from 15.33 from 22.70% in genotype JG 315 of chickpea. Saxena and Saxena (2011) depicted protein content losses from 18 to 21.22% incurred by C. chinensis infestation.…”
Section: Germinationmentioning
confidence: 94%
“…The results are in agreement with Singh and Singh (2020) who reported that the green gram varieties with starch content have higher index of susceptibility. Similar findings were also documented by and Deepika et al (2020).…”
Section: Phenolssupporting
confidence: 89%
“…The results are in agreement with the findings of Sreedhar et al (2020) and they reported that higher per cent of sugars in groundnut varieties are preferred by bruchids. According to Deepika et al (2020), the infestation in stored chickpea varieties is more with increase in the total soluble sugars and vice versa. Results are also in accordance with Kosini et al (2019) and Singh and Singh (2020).…”
Section: Total Soluble Sugars (Tss)mentioning
confidence: 99%
“…Trypsin inhibitor has long been considered as an important anti-nutrient factor (Gatel, 1994), but recently some of them have been found to be beneficial to humans and animals (Kennedy, 1998;Ashton-Rickardt, 2012) or can be used as food processing agents (Boudida et al, 2016;Singh & Benjakul, 2018). In addition, trypsin inhibitor has been found to be partially associated with resistance to the bruchid or pulse beetle (Callosobruchus chinensis) in many legume species, including grass pea (Deepika et al, 2020).…”
Section: Introductionmentioning
confidence: 99%